2016
DOI: 10.1016/j.eneco.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Limited trading of emissions permits as a climate cooperation mechanism? US–China and EU–China examples

Abstract: Recent multilateral climate negotiations have underlined the importance of international cooperation and the need for support from developed to developing countries to address climate change. This raises the question of whether carbon market linkages could be used as a cooperation mechanism. Policy discussions surrounding such linkages have indicated that, should they operate, a limit would be set on the amount of carbon permits that could be imported by developed regions from developing countries. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…These results are evidence of the importance of designing the Chinese ETS wisely. By simulating autarky and linkage scenarios, Gavard et al estimated a sectoral ETS on energy-intensive industries in the EU, the USA, and China [52]. They found that the limit results in different carbon prices between China and Europe or the USA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results are evidence of the importance of designing the Chinese ETS wisely. By simulating autarky and linkage scenarios, Gavard et al estimated a sectoral ETS on energy-intensive industries in the EU, the USA, and China [52]. They found that the limit results in different carbon prices between China and Europe or the USA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 The Kyoto mechanisms have faced serious problems in ensuring environmental integrity (Wara 2008;He & Morse 2010;Kollmuss et al 2015;Simmons & Young 2016). New Zealand's connection to those mechanisms, and our poorly 1 Million tonnes of carbon dioxide equivalent 2 Gavard et al (2016) analyse the potential impacts of volume-limited emissions trading between China and the European Union (EU) or United States. They find that both sets of trading partners can benefit if China captures the rents from differential emission prices and that more ambitious global mitigation can be achieved.…”
Section: International Policy Framework For Carbon Marketsmentioning
confidence: 99%
“…A carbon market linking more countries can lead to larger reductions in abatement costs [21][22][23][24]. However, a carbon market linking regions with similar abatement costs may have limited reductions in abatement costs [25][26][27]. Second, carbon market linkage can increase market liquidity and transaction scales while reducing market fluctuation and avoiding price manipulation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%